Ant diversity inhabited oil palm plantations in a peatland in Sumatra, Indonesia - Asni Johari; M. ASEP HERMANTO; Tia Wulandari (Smujo International, 2021)
Abstract. Johari A, Hermanto MA, Wulandari T. 2021. Ant diversity inhabited oil palm plantations in a peatland in Sumatra, Indonesia. Nusantara Bioscience 13: 158-163. Ant community is one of the soil biotic components with diverse roles, including pollinators, predators, decomposers, parasites, and herbivores. Changes in land use from natural habitats to plantations affect the diversity and composition of ants because these groups are very vulnerable to environmental changes. The purpose of the study was to analyze the diversity of ants (Formicidae) found in peatlands planted with oil palms. The study was conducted on peatland in Gambut Jaya village, Sungai Gelam sub-district, Muaro Jambi district, Indonesia, from October 2019 to May 2020. The research was conducted through surveys in two peatland locations (natural peatland and oil palm plantation) using the purposive sampling technique through transect making, field sampling, sample preparation, and identification. A total of 2,636 ants were collected from natural peatlands, while 3,183 individuals were found in oil palm plantations. Eight ant species were identified from both study sites belonging to four subfamilies: Dolichoderinae, Formicinae, Myrmicinae, and Ponerinae. Among the species, Dolichoderus thoracicus were most dominant, composed of 63.6% in natural peatland and 73.6% in oil palm plantation. The diversity index of ant species in natural peatland was higher (0.97) than that in oil palm plantations (0.88), indicating the change in the abundance and diversity of ant species in oil palm plantations. Therefore, efforts to preserve the habitat of ants by maintaining their microhabitat and resource, as well as conserving the important species such as natural enemies of pests, need to be taken into account in peatland management.